An Assessment of the Design Criteria of Market Areas in Terms Of Urban Space Quality - Tabak Abacilar, Pinar; Yücel Caymaz, Gökçen Firdevs (Street Art & Urban Creativity, 2022)
This study was conducted to determine how the public markets that serve as open urban areas fit themselves among the other functions in the city and how the design criteria could be shaped in a well-organized city. In the study, urban space quality was analyzed over Yeşilköy market (İstanbul), Kemerburgaz Bol Pazar market (İstanbul), and the Braga Market (Portugal) in terms of design criteria. These evaluations were applied by revealing the urban space quality criteria through literature research. In addition, design parameters were created based on site selection, circulation, and street furniture (lighting, landscape, and signing) determined for open market places through design guidelines and existing examples. On-site fieldwork for the examples in Istanbul was carried out. Three different examples discussed in the study were analyzed over the design parameters. The location selection, that is among the design criteria of the market areas, is to some extent important for users to use these areas, but it is not the only indicator on its own. Today’s modern market areas are not only for selling fruits and vegetables, they are created using good design elements and equipped with versatile activities and social areas.